2009
DOI: 10.1007/s12053-009-9041-2
|View full text |Cite
|
Sign up to set email alerts
|

Reducing energy use in the buildings sector: measures, costs, and examples

Abstract: This paper reviews the literature concerning the energy savings that can be achieved through optimized building shape and form, improved building envelopes, improved efficiencies of individual energyusing devices, alternative energy using systems in buildings, and through enlightened occupant behavior and operation of building systems. Cost information is also provided. Both new buildings and retrofits are discussed. Energy-relevant characteristics of the building envelope include window-to-wall ratios, insula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
73
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(74 citation statements)
references
References 37 publications
1
73
0
Order By: Relevance
“…The market and technical risks of the technologies used also contribute to the limited implementations resulting in fewer earned points. Still, significant savings in energy use in new buildings are possible using existing technologies [57]. The concerns also extend to non-economic barriers such as lack of technical expertise for advanced tools and services needed for improving energy efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…The market and technical risks of the technologies used also contribute to the limited implementations resulting in fewer earned points. Still, significant savings in energy use in new buildings are possible using existing technologies [57]. The concerns also extend to non-economic barriers such as lack of technical expertise for advanced tools and services needed for improving energy efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…From design parameter based LSA in previous section, the importance of design parameters to OE of building was understood and it was found that U-value of roof can be the priority target to reduce the OE of building as compared to other design parameters considered in this research, however this information may not result in an energy-efficient optimization process. This is due to EE of element is considerably increased during the optimization of building envelope while increasing the material consumption to satisfy the target thermal properties and reduce OE in buildings [2] [15] [32]. Besides, since the elements made up from different materials with its distinct thermal properties and each element comprised different proportion of EE in the building envelope, it is necessary to understand the uncertainty between thermal properties and EE of building envelope and subsequently the resulted OE-EE relationship of each envelope element.…”
Section: Sensitivity Analysis and Discussionmentioning
confidence: 99%
“…As confirmed by the analyses carried out by a number of authors [11,[28][29][30][31], 30 to 40% of the heat loss from residential buildings in various climatic conditions is discharged into the atmosphere together with the used air via the natural ventilation systems. In order to optimise the performance parameters of the ventilation system and simultaneously minimise heat losses via ventilation in a residential building, it is necessary to determine the unit heat flow driven out of the building together with the used air over one hour.…”
Section: Methodsmentioning
confidence: 88%